Analisis Efektivitas Penerapan Model Make A Match Berbasis Media Puzzle Terhadap Hasil Belajar Siswa SD pada Mata Pelajaran IPS di SD - Farah Annisa; Linda Cibya Rahmawati; Yona Wahyuningsih (Departement of Mathematics Education, 2022)
This research is motivated by the learning model used by the teacher is still using the old learning model. Thus, to make it easier for students to receive subject matter, especially in social studies subjects, a make a match model is applied in learning. When learning material is difficult for students to accept, it will affect student learning outcomes. Based on the results of the study, the application of the make a match learning model can improve student learning outcomes because the model is easy for students to understand and also fun for students.